The Relationship between Sensory Design and the Perceived Value of Service Quality: The Interactive Role of Strategic upgrading an Empirical Study of Retail Stores in Samawah - Kadim, Jasim Rahi; Jahil, Shahad Baqer; Kadhem, Safaa K; Sabti, Yousif Mousa; Neama, Abdullah Abdulmalike (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
The current research aims to know the association between sensory design and  perceived value and the interactive effect of upgrading. The researcher distributed  (60) questionnaires in retail stores in the city of Samawah. The design contributes  to achieving the perceived value of the customer, and this was what the researcher  tried to prove by analyzing the data he obtained on the real role of SD in creating  customer value.
Keywords: Sensory design; Service quality; Perceived value